This is where I leave you - Tropper, Jonathan (London : Orion Books, 2011)
Een Amerikaanse man beleeft privmoeilijke tijden, maar slaat zich daar met glans doorheen.
Oorspr. geb. uitg.: 2010.
Keywords: Adultery -- Fiction; Fathers -- Fiction -- Death; Brothers and sisters -- Fiction